2008
DOI: 10.1093/nar/gkn898
|View full text |Cite
|
Sign up to set email alerts
|

Small non-coding RNAs in Streptomyces coelicolor

Abstract: In bacteria, small RNAs (sRNAs) make important regulatory contributions to an ever increasing number of cellular processes. To expand the repertoire of known sRNAs, we sought to identify novel sRNAs in the differentiating, multicellular bacterium Streptomyces coelicolor. We describe a combined bioinformatic and experimental approach that enabled the identification and characterization of nine novel sRNAs in S. coelicolor, including a cis-encoded antisense sRNA. We examined sRNA expression throughout the S. coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
88
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 51 publications
8
88
0
Order By: Relevance
“…3,100 genes may be transcribed at low levels during exponential growth, perhaps from leaky promoters. Antisense transcripts, which have been identified in S. coelicolor and other bacteria (39,41,42), may also contribute to the low-abundance category.…”
Section: Resultsmentioning
confidence: 99%
“…3,100 genes may be transcribed at low levels during exponential growth, perhaps from leaky promoters. Antisense transcripts, which have been identified in S. coelicolor and other bacteria (39,41,42), may also contribute to the low-abundance category.…”
Section: Resultsmentioning
confidence: 99%
“…Small noncoding RNAs (sRNAs) control a wide variety of cellular processes in bacteria by modulating the stability and/or translation of mRNA targets or by modifying protein activity (269). Combinations of bioinformatic predictions and experimental approaches have facilitated the identification of many sRNAs in S. coelicolor and other species (52,(269)(270)(271), and what little is known about their functions points to a boost in the perceived importance of sRNA-mediated regulation of antibiotic production in the near future.…”
Section: Srnasmentioning
confidence: 99%
“…Combinations of bioinformatic predictions and experimental approaches have facilitated the identification of many sRNAs in S. coelicolor and other species (52,(269)(270)(271), and what little is known about their functions points to a boost in the perceived importance of sRNA-mediated regulation of antibiotic production in the near future. Thus, the overexpression of scr5239, an sRNA recently identified in S. coelicolor, decreased ACT production, whereas depletion of scr5239 increased production (272), and overexpression of cnc2198.1as significantly decreased RED production (273).…”
Section: Srnasmentioning
confidence: 99%
“…The complete genome sequences of several species of Actinobacteria, including two Streptomyces species, S. coelicolor A3(2) (3) and Streptomyces avermitilis (11), facilitated bioinformatics prediction of candidate regions for sRNAs in Streptomyces. Recently, two studies (23,27) reported the identification of sRNAs in S. coelicolor A3(2). Panek et al (23) predicted 32 potential sRNAs, and the expression of 20 of them was detected by reverse transcription (RT)-PCR and DNA microarray analyses.…”
mentioning
confidence: 99%